The Effect of Tax Avoidance and Tax Aggressiveness on Firm Value with Earning Management as a Moderating Variable: Case Study on Consumers Goods Industry (Cyclical and Non-Cyclical Consumers) Sectors Listed on the Indonesia Stock Exchange from 2018 to 2022 - Doni Cahyo Wibowo (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
This study aims to analyze the effect of tax avoidance and tax aggressiveness on firm value in the Consumers Cyclical and Non-Cyclical sectors listed on the Indonesia Stock Exchange from 2018 to 2022, with earning management as a moderating variable. Tax avoidance and tax aggressiveness are strategies used by companies to minimize tax burdens, which are expected to increase corporate profits and ultimately enhance firm value. However, there are differing views on the impact of these strategies on firm value, especially when considering the role of earning management. The study employs the Structural Equation Modeling (SEM-PLS) method, using data obtained from the financial statements of 54 company samples. The results indicate that tax avoidance and tax aggressiveness do not have a significant effect on firm value. However, earning management weakens the impact of tax aggressiveness on firm value, while it does not moderate the relationship between tax avoidance and firm value. These findings contribute new insights to the literature on tax strategy and firm value by highlighting the role of earning management in weakening the effect of tax aggressiveness on firm value. Based on these results, companies are advised to exercise caution in implementing aggressive tax strategies and to ensure that earning management is not overly applied, as it may reduce investor confidence and harm the company’s value.